Tinjauan Pengunduran Diri Pekerja Kontrak: Perspektif dan Aspek Hukum Perburuhan dalam Pemenuhan Hak Pengunduran Diri Pekerja - Juliano Raditya, Jason; Lie, Gunardi (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
Resignation is an act voluntarily or based on personal motives undertaken to leave a position in the company. Resignation by workers is generally caused by differences of opinion or differences of understanding between workers and superiors and employers. Cases of resignations are rife due to frequent errors in terms of communication between the two parties. This study discusses the case of contract workers who resign from a company but do not get their rights. In this case of resignation, the worker does not receive his rights that should have been paid according to Labor Law Legislation. The research method used in this study is juridical-normative legal research. This approach involves the analysis of theoretical frameworks, concepts, and legislation relevant to the research topic. The research approach used is a qualitative approach, namely research procedures that produce descriptive data.